Pengembangan Bahan Ajar Pembentukan Karakter Berbasis Kearifan Lokal di Kelas IV - Tubagus, Nurul Fadillah; Sukmawarti , Sukmawarti (JURNAL PENELITIAN PENDIDIKAN MIPA, 2025)
This research aims to develop character building teaching materials based on local wisdom that are suitable for use in the learning process in fourth grade elementary school. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. However, in this study the ADDIE procedure was used only up to stage 3, namely the development stage. The instrument used to collect data was a validation questionnaire given to several expert validators, namely teaching material expert validators, material expert validators and learning expert validators. The total score obtained from the validation of teaching material experts was 85.4, from the final validation of material experts, namely 82.2 and from learning experts, it was 93. The average score from the experts' assessments was 86.86. From this score, it can be said that the character building teaching materials based on local wisdom that were developed are "very suitable" for use in the learning process in fourth grade elementary school.